High-pitch dual-source paranasal sinus CT in agitated patients with maxillofacial trauma: analysis of image quality, motion artifacts, and dose aspects. (August 2018) - Frellesen, Claudia; Wichmann, Julian L; Tischendorf, Patricia; Scholtz, Jan-Erik; Beeres, Martin; Vogl, Thomas J; Bauer, Ralf W
Background: Image quality benefits from high-pitch scanning in agitated patients by reducing acquisition time. Purpose: To compare image quality and exposure parameters in patients with maxillofacial trauma on second- and third-generation dual-source computed tomography (DSCT). Material and Methods: Four groups were compared. Group 1 was examined on second-generation DSCT (120 kV/50 mAs, pitch 3.0). The other three groups were examined on third-generation DSCT. Group 2 was scanned with 120 kV/50 mAs, pitch 2.2. Automated exposure control (AEC) was used in group 3 and group 4 with pitch factors of 2.2 and 3.0, respectively. Images of third-generation DSCT were reconstructed with iterative reconstruction (IR), of second-generation DSCT with filtered back-projection. CTDIvol, acquisition time, and image quality were compared. Results: Thirty patients were included in each group. Average CTDIvol (2.76 ± 0.00 mGy, 2.66 ± 0.00 mGy, 0.74 ± 0.23 mGy, and 0.75 ± 0.17 mGy) was significantly lower on third-generation DSCT with AEC ( P < 0.001). Subjective image quality was rated worst in group 4 due to strong high-pitch artifacts, while in the remaining three groups it was rated good or very good with good inter-observer agreement (k > 0.64). Average acquisition time was significantly shorter with third-generation DSCT (0.47 s, 0.36 s, 0.38 s, 0.30 s; P < 0.001). Conclusion: Third-generation DSCT yields faster acquisition times and substantial dose reduction with AEC. A pitch of 2.2 should be preferred, as it results in fewer artifacts. If AEC is used, latest IR ensures that diagnostic image quality is guaranteed.